2020
DOI: 10.3390/molecules25194427
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Influenza Virus Activity and Chemical Components from the Parasitic Plant Cuscuta japonica Choisy on Dimocarpus longans Lour.

Abstract: Dodder (Cuscuta spp.) is a parasitic weed damaging many plants and agricultural production. The native obligate parasite Cuscuta japonica Choisy (Japanese dodder) parasitizes Dimocarpus longans Lour., Ficus septica Burm. F., Ficus microcarpa L.f., Mikania micrantha H.B.K. and Melia azedarach Linn, respectively. Five Japanese dodders growing on different plants exhibit slightly different metabolites and amounts which present different pharmacological effects. Among these plants, a significant antiviral activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Apriyanto et al (2015) [34] reported that the longan tree leaf extract possesses activity towards the hepatitis-C virus and minimizing of death rate. Anti-influenza activity has also been noted by the chemical components from the parasitic plant on Dimocarpus longan Lour [35].…”
Section: Anti-microbial Activitiesmentioning
confidence: 96%
See 1 more Smart Citation
“…Apriyanto et al (2015) [34] reported that the longan tree leaf extract possesses activity towards the hepatitis-C virus and minimizing of death rate. Anti-influenza activity has also been noted by the chemical components from the parasitic plant on Dimocarpus longan Lour [35].…”
Section: Anti-microbial Activitiesmentioning
confidence: 96%
“…Consequently, inflammation and inflammation-mediated diseases are minimized via mediating the H 2 O extract of longan pericarp [33]. Longan leaf extract and specific extracted chemical components possess significant activity towards the HCV (hepatitis-C virus) and influenza virus infection, respectively [34,35]; lipopolysaccharide (LP-1, 2) derived from the longan pulp possesses immunomodulatory activity [12]. Here, ellagic acid showed the most potent anti-fungal activity, longan seeds have better anti-fungal activity against opportunistic yeast, for example, Candida species and Cryptococcus neoformans [36].…”
Section: Introductionmentioning
confidence: 99%
“…Cardioprotective, neuroprotectiv anti-inflammatory, anticancer antimicrobial and antioxidative [43 7. 1-monopalmitin C19H38O4 Antiviral [47] Cardioprotective, neuroprotective, anti-inflammatory, anticancer, antimicrobial and antioxidative [43][44][45][46] 7.…”
Section: C20h30o2mentioning
confidence: 99%
“…Cardioprotective, neuroprotectiv anti-inflammatory, anticancer, antimicrobial and antioxidative [43 7. 1-monopalmitin C19H38O4 Antiviral [47] Antiviral [47] 8. 24 8.…”
Section: C20h30o2mentioning
confidence: 99%